2017
DOI: 10.17696/2318-3691.24.4.2017.680
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Sociodemográficos E Clínicos Dos Pacientes Que Tiveram Perda Do Enxerto Renal

Abstract: Fatores sociodemográficos e clínicos dos pacientes que tiveram perda do enxerto renalSociodemographic and clinical factors of patients who have lost kidney grafting ARTIGO ORIGINAL Resumo Introdução: O transplante renal é uma terapia renal substitutiva que proporciona resultados mais expressivos na qualidade de vida do paciente dialítico. A sobrevida do enxerto depende do tipo de doador (falecido ou vivo), se houve complicações no pós-operatório e se adquiriu infecções (trato urinário, do trato respiratório, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…26 Systemic arterial hypertension, when uncontrolled, also presents risks for graft loss, since decompensated SAH causes tubular necrosis and other functional and/or structural complications of target organs. 28 It is also added that, regardless of the comorbidities that the patient has, prior to performing the surgery, the patient undergoes an evaluation to analyze if he has clinical conditions to perform a surgery and, if any alteration is identified that puts him at risk , the transplant will not happen and the next one on the list will benefit.…”
Section: Resultsmentioning
confidence: 99%
“…26 Systemic arterial hypertension, when uncontrolled, also presents risks for graft loss, since decompensated SAH causes tubular necrosis and other functional and/or structural complications of target organs. 28 It is also added that, regardless of the comorbidities that the patient has, prior to performing the surgery, the patient undergoes an evaluation to analyze if he has clinical conditions to perform a surgery and, if any alteration is identified that puts him at risk , the transplant will not happen and the next one on the list will benefit.…”
Section: Resultsmentioning
confidence: 99%